A constituição discursiva da morte na obra de Hilda Hilst - Ferreira, Jaciane Martins (2016)
The book Estar sendo. Ter sido (To be being. To have been), from Hilda Hilst (Hilst 2006a) has Vittorio as character, a sixty-old-man that broke up with his wife and changed to a beach house with his brother Matias and his son Júnior. The narrative is about his life and his memories, broken in two parts; the first one shows the companionship among them; the second one is about a bigger isolation, that is, he is only with a made and a barman. Vittorio also breaks with the social rules and starts living a kind of death in life. When he reports his memories, he brings characters from others Hilst’s books to his story, as Crassus and Kraus, from the book Contos D’Ecárnios e textos grotescos (Scorn Tales /grotesque texts) (Hilst, 2002a); Cordélia and Stamatius, from Cartas de um sedutor (Letters from a seducer) (Hilst, 2002b); Edemir, from Caderno rosa de Lory Lambi (The pink notebook of Lory Lambi) (Hilst, 2005); Hillé, from the book A obscena Senhora D. (The obscene Lady D.) (Hilst, 2001); Kadek, from the tale Vicioso Kadek published in the collection of short stories entitled Rútilos (Hilst, 2010) and Kadosh, from the book Kadosh (Hilst, 2002c). The thesis presented here started by the desire to understand the discursive functioning of death within these cited Hilst’s works. Thus, in our analysis, we discuss about death in a self-writing frame, the characters position as subjects, their historic constitution, the relationship with death also permeated by the memory, the way it emerges in some of her texts, the relationship with the authorship and the sex, as the characters are interconnected and show their position in bio-historic process (FOUCAULT,1999). Therefore, in order to achieve our goals, we analyzed forty-six excerpts in three chapters. The corpus was built from extracts of the seven mentioned books, we use the assumption about the statement and the archive (FOUCAULT, 2008) as a methodological contribution. Though, in three chapters, we analyzed the corpus thinking about Vittorio’s relationship with his relatives and the way he puts himself in a possible death place when he breaks with the social protocols; the relation among death, sex and authorship and how the subjects constitute themselves through memories which are social stablished; at last, we thought about the discursive relationship between the subject and the body, the old body, considered as a useless body in our society. In this way, we analyzed the subject in order to understand his self’s searching which comes through a self-writing.